PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP HARGA ECERAN TERTINGGI (HET) GULA PASIR DI PASAR CIK PUAN KOTA PEKANBARU - Albinus Siahaan; Hayatul Ismi; Hengki Firnanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Business actors often use consumers as objects of business activities to reap the maximum benefits. Usually business actors carry out promotional tips, sales methods, and implementation of standard agreements that harm consumers. However, in reality, education for consumers is still relatively minimal and consumers' awareness of their rights and obligations is still low. Sugar is an important commodity for Indonesia. Apart from being one of the staple foodstuffs, sugar is also a source of calories for people besides rice, corn and tubers. As the main sweetener, sugar is also used as a raw material in the food and beverage industry. Until now, the existence of artificial sweeteners and other sweeteners can not completely replace the existence of sugar.The problems that the authors make the basis for in this study are how to protect sugar consumers in Cik Puan Market, Pekanbaru City based on the Regulation of the Minister of Trade of the Republic of Indonesia Number 96 of 2018 concerning Reference Purchase Prices at Farmers' Level and Reference Sales Prices at the Consumer Level and Law Number 8 of 1999 concerning Consumer Protection and what efforts can be made by consumers on the sale of sugar in Cik Puan Market, Pekanbaru City This type of research used by the author is sociological legal research, which is also called doctrinal legal research. This normative research is a study that discusses legal principles, legal systematics, the level of legal synchronization, legal history and legal comparisons.From this sociological legal research, the author is interested in conducting research using legal systematic criteria. The results of Article 8 paragraph 1 letter f of Law Number 8 of 1999 concerning Consumer Protection which states that business actors are prohibited from producing and / or trading goods and / or services that do not include promises that are stated on the label, etiquette, description of the goods and / or services. Article 62 paragraph 1 of Law Number 8 Year 1999 concerning Consumer Protection, business actors who violate this are subject to a maximum criminal sentence of 5 (five) years or a maximum fine of IDR 2,000,000,000 (two billion). Second, in the efforts of consumers to get consumer protection against the sale of sugar above the highest retail price, they can make a report to related parties, in this case the Pekanbaru City Trade Office.Keywords: Market, HET, Sugar